POST- NAUPLIAR STAGES OF"ACARTIA (ACARTIELLA) FAOENSIS" , KHALAF (COPEPODA : CALANOIDA ), FROM KHOR AL-ZUBAIR SOUTH OF IRAQ - Khalaf, TALIB A. (Iraqi Journal of Aquaculture, 2022)
Acartia (Acartiella ) faoensis has been established by the author,(Khalaf, 1991) from Khor Al-Zubair and Khor Abdulla NW Arabian Gulf. It passes through six copepodite stages identical with most other copepods; the last stage is the adult. Description, illustration and measurements for every stage are presented.